2022
DOI: 10.31258/ijesh.4.1.1-13
|View full text |Cite
|
Sign up to set email alerts
|

A Framework of Contingencies Factors, Government Support and Management Accounting Practices in Malaysian Small and Medium-Sized Enterprises

Abstract: Small and medium-sized enterprises (SMEs) are critical in developing countries, as they create significant job opportunities and contribute to global economic development. Numerous Malaysian SMEs are struggling to survive in the aftermath of the COVID-19 outbreak. As a result, the adoption of management accounting practices (MAPs) plays an important role in supporting decision making, which aids in the sustainability of SMEs' economic growth and leads to long-term performance. However, there is limited researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
0
5
0
2
Order By: Relevance
“…In 2021, the SMEs contributed 37.4% to the Malaysia's Gross Domestic Product (GDP) and provided 47.8% jobs out of the country's total jobs (DOSM, 2022). These clearly demonstrated that the SMEs are significant to Malaysia's employment rate, as well as economic growth (Abdullah et al, 2022).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…In 2021, the SMEs contributed 37.4% to the Malaysia's Gross Domestic Product (GDP) and provided 47.8% jobs out of the country's total jobs (DOSM, 2022). These clearly demonstrated that the SMEs are significant to Malaysia's employment rate, as well as economic growth (Abdullah et al, 2022).…”
Section: Introductionmentioning
confidence: 90%
“…Small and medium-sized enterprises (SMEs) are considered as one of the crucial economic contributors to the economy growth of the country (Isa & Razak, 2021). These enterprises have significantly created tremendous job opportunities and considered the backbone of the country's economic development (Abdullah, Mirza, Krishnan, Zakaria, & Morris, 2022). Therefore, over a few decades, researchers of accounting and management area have been consistently placing efforts in investigating the SMEs (Azudin & Mansor, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dalam mekanisme penyalurannya, bantuan sosial dilaksanakan oleh kementrian/ lembaga yang telah diatur dalam PMK Nomor 228/PMK.05/2016. Hasil penelitian terdahulu menunjukkan bahwa strategi bantuan sosial berdampak positif terhadap peningkatan kinerja usaha kecil (Haykal et al, 2022;Joo & Min, 2022;Nik Abdullah et al, 2022).…”
Section: Kajian Pustaka Dan Pengembangan Hipotesis Strategi Bantuan S...unclassified